Neuropsychological profile in tuberous sclerosis complex: a study of clinical and cognitive variables in a cohort from Brazil - Cardozo, Laís Faria Masulk; Schwind, Mariana Richartz; Pereira, Ana Paula Almeida de; Dufner-Almeida, Luiz Gustavo; Haddad, Luciana Amaral; Bruck, Isac; Antoniuk, Sérgio Antonio (Arquivos de Neuro-Psiquiatria, 2024)
Background Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder with a wide clinical, cognitive, and behavioral expressivity.Objective To assess the neuropsychological profile of individuals clinically diagnosed with TSC and the factors that could significantly impact their cognitive development.Methods A total of 62 individuals with ages ranging from 3 to 38 years were followed up in a tertiary attention hospital in Southern Brazil, and they were assessed using a standard battery and the Vineland Adaptive Behavior Scales, when intellectual disability was observed.Results History of epilepsy was found in 56 participants (90.3%), and 31 (50%) presented an intellectual disability. Among the other half of TSC individuals without intellectual disability, 8 (12.9%) presented borderline classification, 20 (32.2%) presented average scores, and 3 (4.8%) were above average. In total, 17 participants (27.4%) fulfilled the diagnostic criteria for autism spectrum disorder. The results of the multiple linear regression analysis suggested that seizures, age at diagnosis, visual perception, and general attention significantly impact cognitive performance indexes.Conclusion The present study suggests that the occurrence of epileptic seizures and older age at diagnosis contribute to higher impairment in the domains of cognitive development, underlining the importance of early diagnosis and the prevention of epileptic seizures or their rapid control. The development of attentional skills, visual perception, and executive functions must be followed up.
Keywords: Tuberous Sclerosis; Neurocutaneous Syndromes; Neuropsychology; Cognition